Hey there!
If x = -3 then replace "x" with -3
New equation: -3^-2
(-1 × 3)^-2
(-1 / 3 )× 3
3 × 3 = 3^3 = 9 (Solving for your denominator)
(-1/3)^2
= (1/9)
This your answer is: 1/9
Good luck on your assignment and enjoy your day!
~LoveYourselfFirst:)
44 cm
Explanation: scale is 3 cm: 22cm if the drawing is two times that which would be 6 it means you would have to times 22cm by 2 22x2=44
Answer:
2 equations
28.8/100*75 = $21.6 - 10% 21.6/100*90 = $19.44
Step-by-step explanation:
First one we determine the 25% ans second we deduct 10% from that result.
Answer:
b) 3 and 4
Step-by-step explanation:
square root of 13 =3.605551275
3xy^z: exponent is not a nonnegative int.
r-2s: it is not a product
(ab)^1/2: exponent is not a nonnegative int.